Htr1b is necessary for normal retinal function in mice - Gibson, Solomon E.; Tao, Xiaofeng; Shen, Guofu; Ma, Justin; Park, Yong H.; Polo-Prieto, Maria; Frankfort, Benjamin J. (Frontiers in Cellular Neuroscience, 2025)
IntroductionSerotonin (5-HT) is a neurotransmitter that is involved in retinal development, physiology, and vision, yet the specific contribution of individual 5-HT receptors to retinal function is poorly characterized. We identified 5-HT receptor 1B (Htr1b) as a potential key regulator of serotonergic signaling in the retina.MethodsHtr1b localization was examined using RNAseq and in situ labeling. Retinal structure was assessed using histology and SD-OCT. Visual function was evaluated using optomotor behavioral experiments. Retinal function was characterized in vivo using electroretinography (ERG) and ex vivo using multielectrode array (MEA) recordings.ResultsHtr1b transcript and HTR1B protein localized primarily to the inner retina and RGCs. While Htr1b–/– mice displayed normal retinal anatomy, they exhibited visual deficits in contrast sensitivity and visual acuity. ERG recordings revealed that RGCs had latency delays and reduced sensitivity to changes in light intensity. MEA analysis showed altered RGC firing patterns and increased variability following 5-HT application. These effects were cell-type specific: Htr1b–/– ON RGCs showed elevated basal firing rates while Htr1b–/– OFF RGCs showed reduced 5-HT responses.DiscussionThese findings demonstrate that Htr1b is necessary for normal retinal serotonergic signaling and contributes to the regulation of RGC excitability and visual sensitivity.